Eco-Friendly Car Fragrance: Coffee Bean Innovation Boosts Local MSMEs: Pengharum Mobil Ramah Lingkungan: Inovasi Biji Kopi Dongkrak UMKM Lokal - Hamdi, M. Sukron; Satrio Sudarso , Satrio Sudarso; Sabila, Nauly; Hidayatulloh, Muhamad Ananta; Wijaya, Rama Adi (Proceedings of The ICECRS, 2025)
General Background: Coffee-producing regions often face challenges in maximizing the economic potential of their agricultural output, particularly when surplus or defective beans are discarded as waste. Specific Background: Kalipucang Village, Tutur District, Pasuruan Regency, has untapped potential in its coffee-based industries, yet local MSMEs struggle with product diversification and value addition. Knowledge Gap: Limited innovation in utilizing unused coffee beans hinders the development of sustainable, value-added products that align with circular economy principles. Aims: This study aims to empower the local MSME Ko-Pucang through the development of a coffee-based car freshener that leverages the natural deodorizing properties and aromatic appeal of coffee beans. Results: Employing a Research and Development (R&D) approach, the program progressed through problem identification, training on formulation using coffee extract and alcohol, product testing for scent longevity and absorption effectiveness, and marketing strategy development. The resulting prototype demonstrated a long-lasting, eco-friendly fragrance and received favorable user feedback for its natural aroma and calming effect. Novelty: This initiative introduces an innovative, sustainable use of coffee waste by transforming it into a high-value, marketable product, marking a shift from traditional coffee-based offerings. Implications: The findings affirm that strategic product diversification can bolster MSME resilience, increase income, and reinforce regional identity, while contributing to broader sustainable development goals through waste reduction and circular economic practices. Keywords: Coffee Waste, MSMEs, Product Diversification, Car Freshener, Circular Economy Highlights: Coffee-based car freshener adds value to unused beans sustainably. MSME empowerment through innovation and marketing strategies. Eco-friendly product supports circular economy and regional branding.